Pengaruh Dukungan Keluarga TerhadapTingkat Kecemasan Anak Sakit Kanker Di RsudDr. Moewardi Surakarta - Putranti, Eka, Endang Zulaicha Susilaningsih, S.Kp.,M.Kep (2016)
Children with cancer his psychological are not much different from adults such as easily agitated, depressed, and fearful about the future. Children will fell sad for not being able to interact like normal kids. They also behave temperrament and uncooperative due insufficient understanding of disease. Family support is one factor that can assist children in dealing anxiety. Family support can lower childrens anxiety levels as a results of hospitalization and cause children more likely to cooperate with medical treatment. This research aims to determine the relationship of family support for childrens anxiety levels in cancer pain in RSUD Dr. Moewardi Surakarta. This research uses descriptive correlative method with cross sectional survey design. Population in this research were 116 children. The sample 35 children with the accidental of sampling technique use of sampling. The research instruments used questionnaire family support and children's anxiety cancer patients who have a valid and reliable. Data analysis using Spearman rank correlation test for an error rate of 5%. Study result : the relationship of family support for childrens anxiety levels in cancer pain in RSUD Dr. Moewardi Surakarta most with enough support (54,3%), most with a moderate level of anxiety (71.4%). Spearman rank correlation (rho) results at (-) 0,449 with a significance (p value) = 0,007. Conclusion: there is a significant negative correlation between family support for children's anxiety levels of cancer pain in RSUD Dr. Moewardi Surakarta.